Variation in pre-harvest sprouting tolerance and fresh seed germination in mungbean (Vigna radiata L.) genotypes. Issue 5 (16th November 2017) - Lamichaney, Amrit; Katiyar, Pradip Kumar; Laxmi, Vijay; Pratap, Aditya
Abstract: Mungbean seeds, despite being protected inside the pod, are susceptible to pre-harvest sprouting (PHS) following rainfall due to lack of fresh seed dormancy (FSD), which deteriorates the quality of the seed/grain produced. Therefore, development of mungbean cultivars with short (10–15 days) period of FSD has become important to curtail losses incurred by PHS. In this study, we investigated variations in PHS, fresh seed germination (FSG) and activity of α -amylase enzyme in diverse mungbean genotypes. There was a wide variation in PHS tolerance and FSG among 163 genotypes examined and 14 genotypes were found to be tolerant (<20%) to PHS. Seed germination in a pod, a measure used to evaluate PHS, varied from 7.14% in germplasm accession Chamu 4 to 82.52% in cultivated variety IPM 2–3. There was a marked increase in α -amylase activity in genotypes showing high FSG and PHS, especially at 48 and 72 h after germination as compared with PHS tolerant genotypes. Therefore, α -amylase can be used as an effective biochemical marker to evaluate a large number of mungbean genotypes for FSD and PHS. Also, the variation in seed germinability as found in this study could be further used for mungbean improvement programme.